ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DENGAN MENGGUNAKAN INCOME STATEMENT APPROACH DAN VALUE ADDED APPROACH: (Studi Kasus Bank Muamalat Indonesia Cabang Tegal) - Ahmad Faqih Udin; Seli Aenina (Fakultas Ekonomi dan Bisnis Islam, 2019)
The objectives of this study are to analyze the differences in financial performance of Islamic bank by using the income statement approach and value added approach on financial ratios. Financial ratios used consisted of ROA, ROE, the ratio between the total net income by total earning assets, NPM, and BOPO. Object used in this research is PT. Bank Muamalat Indonesia Cabang Tegal. The population of this research is the financial statements PT. BMI Cabang Tegal, while the sample was consolidated financial statements year 2015-2017 for each of Income Statement Approach and Value Added Approach. Analysis tool used to prove the hypothesis of this study is an independent sample t-test. The results showed that the average financial ratio (ROA, ROE, net profit ratio of productive assets, and NPM) there are significant differences between the Income Statement Approach and Value Added Approach, while the BOPO ratio between the Income Statement Approach and the Value Added Approach there is not a difference. But when viewed in the overall level of profitability shows that there are significant differences between the Income Statement Approach and Value Added Approach.